Winning and Losing in Large-Scale Software Development: A Multi-Decade Perspective. - Scacchi, Walt (Computer (00189162), 2018)
What have we learned more than 50 years into the life history of software development? This article highlights some lessons about what has worked and what hasn’t. It provides a short history of large-scale software development and covers topics ranging from software seen as intellectual property to software maintenance and evolution.